PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LEVERAGE, DAN REPUTASI KAP TERHADAP TIMELINESS : OPINI AUDIT SEBAGAI PEMODERASI: THE INFLUENCE OF PROFITABILITY, COMPANY SIZE, LEVERAGE, AND KAP'S REPUTATION ON TIMELINESS: AUDIT OPINION AS A MODERATION - Asnizonia, Febby; Anisma, Yuneita; Silalahi, Sem Paulus (Universitas Riau, 2022)
This study investigates and assesses the effects of profitability, business size, leverage, and KAP's reputation on the timeliness of financial reporting using the auditor's opinion as a moderating variable. The study population consists of manufacturing companies in the consumer products industry that were listed on the Indonesian Stock Exchange in 2018–2020. The sampling method employed in this study to create a sample of 51 businesses was purposeful sampling. The analysis technique is logistic regression analysis using moderated regression analysis and SPSS version 26. The results of this study show that profitability, firm size, or KAP's reputation have no bearing on the accuracy of financial reporting. Leverage also affects how quickly financial reports are produced. These points of view are insufficient to mitigate the impact of KAP's profitability or scale, leverage, and reputation on the promptness of financial reporting.